1980
DOI: 10.1002/marc.1980.030010603
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the anionic polymerization of methyl methacrylate in 1,2‐dimethoxyethane

Abstract: Earlier kinetic investigations on the anionic polymerization of methyl methacrylate (MMA) in tetrahydrofuran (THF) showed that under appropriate conditions the reaction can be regarded to proceed in an ideal manner1-4). The Arrhenius plots of the rate constants for the propagation reaction of ion pairs with both Na+ and Cs+ as counterions exhibit straight lines which can be regarded to be identical within the limits of experimental error; thus no evidence for the existence of more than one kind of ion pair is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
16
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(18 citation statements)
references
References 11 publications
2
16
0
Order By: Relevance
“…It is also known that solvent polarity largely affects the reactivity and identity of the propagating species. 39 It was shown that increasing the solvent polarity causes a decrease in isotacticity and a narrowing of molecular weight distribution of PMMA. 40 The polymerization of MMA in toluene/THF (9/1 v/v) mixed solvent was carried out in both the presence and absence of LiClO 4 using DPHLi as an initiator at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…It is also known that solvent polarity largely affects the reactivity and identity of the propagating species. 39 It was shown that increasing the solvent polarity causes a decrease in isotacticity and a narrowing of molecular weight distribution of PMMA. 40 The polymerization of MMA in toluene/THF (9/1 v/v) mixed solvent was carried out in both the presence and absence of LiClO 4 using DPHLi as an initiator at different temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, many attempts have been made to affect the aggregation equilibria in the polymerization of MMA by using chelating solvents and ligands. Kinetic studies of the polymerization of MMA in the chelating solvent 1,2-dimethoxyethane (DME) of Müller et al [1,[16][17][18] resulted in higher propagation rate constants for Na + and Cs + but lower ones with Li + as counterion. The increase in rate for the larger counterions may be explained by deaggregation of dimers or by an increase of the interionic distance in the ion pairs leading to higher reactivity.…”
Section: Introductionmentioning
confidence: 99%
“…It is, thus, important to decrease the aggregation or at least to suppress the formation of higher aggregated ester enolates which are of extremely low reactivity. For this aim, polar solvents, especially THF or 1,2-dimethoxyethane, and larger counterions have been used, resulting in a controlled polymerization. , In some more recent approaches, various ligands have been introduced as additives. σ-Ligands, i.e., electron donors, specifically solvate the Li atoms of the ester enolate individual molecules or aggregates, thus preventing their further aggregation.…”
Section: Introductionmentioning
confidence: 99%